Acceptance and Commitment Therapy: Applications for Educational Psychologists within Schools. Issue 3 (3rd July 2018) - Gillard, Duncan; Flaxman, Paul; Hooper, Nic
ABSTRACT: Guidance for schools regarding the promotion and enhancement of psychological wellbeing represents an invitation to intervene to promote effective, evidence-informed, whole-school approaches for school staff, students and parents. With its transdiagnostic approach and evidence from empirical literature, Acceptance and Commitment Therapy (ACT) is asserted as a coherent psychological model that has potential to support schools in developing effective and sustainable practices to promote psychological wellbeing. Three ways of applying ACT within educational contexts are discussed, demonstrating potential utility of the model: supporting school staff wellbeing; targeted interventions for children and young people; and a potential universal application, through the development of an ACT-based emotional health and wellbeing curriculum.